Alternativa para la detección de celos en el ganado bovino mediante el potencial uso de caninos (monografía). - Escobar Ramírez, Anthony Ricardo; Olaya Gómez, Oscar Andrés; Tarquino Ruíz, Jhon Sebastián (Universidad Antonio Nariño, 2021)
Propia